EFEKTIVITAS KURKUMIN SEBAGAI ANTIOKSIDAN DAN INHIBITOR MELANIN PADA KULTUR SEL B16-F1 - Sugiharto; Arbakariya Ariff; Syahida Ahmad; Muhajir Hamid (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
Melanin inhibitors have become increasingly important ingredients in medication and cosmetics for the prevention of hyperpigmentation. In the last few years, a huge number of natural herbal extracts have been tested as inhibitors of melanin synthesis and some of these effects are related to the antioxidant properties. The objectives of this study were to determine of curcumin properties as antioxidant activity and melanin inhibitors. In this study, our data indicated that antioxidant assay with DPPH showed IC50 was 16,05 μg/ml. In the absence of α-MSH (α-Melanocyte Stimulating Hormone), melanin content assay in cell B16-F1 indicated that the highest activity of curcumin to reduce melanin content of 45,67% at 25 μg/ml. Meanwhile, in the presence of α-MSH at the same concentration indicated that the highest activity was 53,87%. Based on the data, curcumin has potential properties as antioxidant activity and melanin inhibitor.